Entropy, environment and resources: an essay in physico-economics - Faber, Malte; Niemes, Horst; Stephan, Gunter (Springer, 1995)
This book analyzes environmental protection and resource use in a comprehensive framework where not only economic but also natural scientific aspects are taken into consideration. The special features of the book are (i) that the authors utilize a natural scientific variable, entropy, to characterize the economic system and the environment, (ii) that environmental protection and resource use are analyzed in combination, and (iii) that a replacement of techniques over time is analyzed. The authors investigate the use of the environment both as a supplier of resources and as a recipient of pollutants with the help of thermodynamic relationships. The book therefore provides a new set of tools for environmentalists and economists
Keywords: Kapitaltheorie; Wiener Schule; Rohstoffverbrauch; Entropie; Umweltökonomie